Aggressive forms of periodontitis secondary to systemic disorders. (June 2014) - Khocht, Ahmed; Albandar, Jasim M.
Abstract: A number of systemic disorders increase a patient's susceptibility to destructive periodontitis and have impacts on periodontal disease progression and severity. The underlying factors are usually genetic and are mainly related to alterations in the immune response and in certain endocrine functions, leading to various syndromes in which periodontitis and/or early tooth loss are secondary manifestations. Neutrophils are important immune defense cells that play a significant role in controlling the spread of microbial plaque infections in the dentogingival region. This review focuses on a selected group of systemic disorders that are associated with alterations in either neutrophil counts (quantitative disorders) or function (qualitative disorders), and defects in the mineralization of bone and dental tissues. In most of these diseases controlling the periodontal disease progression is very challenging. Proper diagnosis is a prerequisite for proper management of the periodontal problem. Future advances in research, including gene targeting and the resolution of enzyme deficiencies, may bring about remedies of the underlying systemic disorders and may significantly improve the outcome of periodontal treatment in these patients.